2017
DOI: 10.1534/g3.117.041632
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Mediated Reverse Genetic Screen IdentifiedDrosophilaChaperones Regulating Eye and Neuromuscular Junction Morphology

Abstract: Accumulation of toxic proteins in neurons has been linked with the onset of neurodegenerative diseases, which in many cases are characterized by altered neuronal function and synapse loss. Molecular chaperones help protein folding and the resolubilization of unfolded proteins, thereby reducing the protein aggregation stress. While most of the chaperones are expressed in neurons, their functional relevance remains largely unknown. Here, using bioinformatics analysis, we identified 95 Drosophila chaperones and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 64 publications
(78 reference statements)
1
24
0
1
Order By: Relevance
“…Like Hsp23, Hsp26 also falls into the sHsp group with high CNS expression ( Figure 2 B) and is one of the sHsps with an essential developmental role [ 2 ]; as revealed by pan-neural knockdown, Hsp26 plays a role in neural development and in particular in the proper formation of NMJs. The Hsp26 loss of function results in an adversely affected presynaptic cytoskeleton, and a reduced number of synaptic buttons at NMJs.…”
Section: Functions Of Shsps Expressed In the Developing Nervous Symentioning
confidence: 99%
See 3 more Smart Citations
“…Like Hsp23, Hsp26 also falls into the sHsp group with high CNS expression ( Figure 2 B) and is one of the sHsps with an essential developmental role [ 2 ]; as revealed by pan-neural knockdown, Hsp26 plays a role in neural development and in particular in the proper formation of NMJs. The Hsp26 loss of function results in an adversely affected presynaptic cytoskeleton, and a reduced number of synaptic buttons at NMJs.…”
Section: Functions Of Shsps Expressed In the Developing Nervous Symentioning
confidence: 99%
“…This specific muscular expression prompted us to test for dCryAB functions. It was recently found that ubiquitous RNAi knockdown of l(2)efl / dCryAB could lead to lethality [ 2 ]. Consistent with this, muscle-specific RNAi attenuation of dCryAB leads to severe morphological and ultrastructural defects in body wall muscles ( Figure 5 ).…”
Section: Roles Of Shsps Expressed In Developing Musclesmentioning
confidence: 99%
See 2 more Smart Citations
“…HSPs are molecular chaperones that represent an intracellular protein quality system to maintain cellular protein homeostasis (proteostasis), preventing aggregation and promoting protein de novo folding or refolding and degradation of misfolded proteins [8]. In addition, HSPs participate in developmental functions in a stress-independent manner [9,10]. In Drosophiladevelopment small Heat Shock proteins (sHsps) have a specific temporal and spatial pattern of expression [10].…”
Section: Introductionmentioning
confidence: 99%